Plasma CXCL3 Levels Are Associated with Tumor Progression and an Unfavorable Colorectal Cancer Prognosis - Can Cui; Rui Zhang; Feng Gu; Yunfeng Pei; Li Sun; Yueyang Huang; Guoping Niu; Jian Li (Journal of Immunology Research)
Background. The CXC chemokines belong to a unique family of chemotactic cytokines that influence the initiation, progression, and clinical outcome of many tumor types. Herein, we investigated the association of the CXC-chemokine ligand 3 (CXCL3) with tumor progression and an unfavorable prognosis for colorectal cancer (CRC). Methods. The quantitative real-time polymerase chain reaction was used to explore the expression of CXCL3 in CRC tissue, adjacent tissue, and plasma. The usefulness of plasma levels of CXCL3 for the diagnosis of CRC was evaluated by receiver operating characteristic curve analysis. Pearson’s correlation analysis assessed relationships among plasma CXCL3, cancer tissue CXCL3, and plasma carcinoembryonic antigen (CEA). Kaplan–Meier analysis was used to assess the survival of CRC patients with high and low expression levels of CXCL3. Survival differences were compared by log-rank test. Results. Initial analysis of the GSE156720 dataset identified CXCL3 as the most enriched CXCL gene in CRC patients. Higher CXCL3 levels were detected in CRC tissue than in adjacent tissue (P<0.001). Compared to healthy controls, CRC patient plasma CXCL3 levels were higher (P<0.001). The area under the curve was 0.81 with a sensitivity of 0.71 and specificity of 0.82, distinguishing CRC from other tumor types. Plasma CXCL3 was positively related to CXCL3 in cancer tissue (r=0.78, P<0.01), and also to plasma CEA (r=0.50, P<0.01). Plasma CXCL3 was also related to tumor size (P=0.034), staging (P<0.001), tumor stage (P=0.003), differentiation (P=0.001), and lymph node metastasis (P=0.007), but not to sex (P=0.853), age (P=0.691), tumor site (P=1.347), or distant metastasis (P=1.218). Conclusions. CXCL3 levels were increased in CRC patients, with plasma CXCL3 levels associated with tumor progression and an unfavorable CRC prognosis. The results of this study suggest that plasma CXCL3 may be a novel diagnostic and prognostic biomarker for CRC.